2017
DOI: 10.1186/s12943-017-0594-y
|View full text |Cite
|
Sign up to set email alerts
|

Dclk1, a tumor stem cell marker, regulates pro-survival signaling and self-renewal of intestinal tumor cells

Abstract: BackgroundMore than 80% of intestinal neoplasia is associated with the adenomatous polyposis coli (APC) mutation. Doublecortin-like kinase 1 (Dclk1), a kinase protein, is overexpressed in colorectal cancer and specifically marks tumor stem cells (TSCs) that self-renew and increased the tumor progeny in Apc Min/+ mice. However, the role of Dclk1 expression and its contribution to regulating pro-survival signaling for tumor progression in Apc mutant cancer is poorly understood.MethodsWe analyzed DCLK1 and pro-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(122 citation statements)
references
References 48 publications
6
115
1
Order By: Relevance
“…Double cortin‐like kinase 1 (DCLK1, formerly known as DCAMKL1), a member of the protein kinase superfamily and the double cortin family, was initially identified as a critical regulator of neurogenesis and neuronal migration . Recently, DCLK1 has been identified as a tumor stem cell marker in CRC, pancreatic cancer and other cancers . DCLK1 protein is highly expressed in several types of cancers, including CRC, pancreatic cancer, hepatocellular carcinoma (HCC), and renal clear cell carcinoma (RCC) .…”
Section: Introductionmentioning
confidence: 99%
“…Double cortin‐like kinase 1 (DCLK1, formerly known as DCAMKL1), a member of the protein kinase superfamily and the double cortin family, was initially identified as a critical regulator of neurogenesis and neuronal migration . Recently, DCLK1 has been identified as a tumor stem cell marker in CRC, pancreatic cancer and other cancers . DCLK1 protein is highly expressed in several types of cancers, including CRC, pancreatic cancer, hepatocellular carcinoma (HCC), and renal clear cell carcinoma (RCC) .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, accumulating evidence suggests that long-lived DCLK1þ tuft cells may be responsible for colorectal cancer development by participating as tumor-initiating populations with persistent Wnt activation (8). DCLK1 was determined to be responsible for cancer progression via the enhancement of survival (44), self-renewal (44), and epithelial-mesenchymal transition (45,46). Moreover, clinical studies in patients with colorectal cancer demonstrated that DCLK1 was expressed in low-grade adenomas, and its levels increased with worsening severity of dysplasia (47).…”
Section: Discussionmentioning
confidence: 99%
“…In a study on CRC metastasis, Gao et al reported that DCLK1 expression was significantly increased in primary CRC and in lymphatic metastases compared with normal colorectal specimens, and moreover, DCLK1 mRNA levels in CRC were significantly correlated with lymph node metastasis and TNM stage (10). DCLK1 expression has also been strongly associated with EMT (18,20). Although a number of genetic studies on DCLK1 have been reported, only few reports have investigated the behavior and distribution of DCLK1 expression in human CRC tissues.…”
Section: Discussionmentioning
confidence: 99%